Exchange Rates and Liquidity Risk - EVANS, Martin D.D. (Journal of Advanced Studies in Finance; Vol 11 No 2 (2020): JASF Volume XI Issue 2(22) Winter 2020DO - 10.14505//jasf.v11.2(22).08, 2020)
I use Forex trading data to study how risks associated with the lack of liquidity contribute to the dynamics of 17 spot exchange rates through their time-varying contributions to risk premia. I find that liquidity risk matters. All the foreign exchange risk premia compensate investors for exposure to liquidity risk; and, for many currencies, exposure to liquidity risk appears to be more important than exposure to the traditional carry and momentum risk factors. I also find that variations in the price of liquidity risk make economically important contributions to the behavior of individual foreign currency returns: they account for approximately 34%, on average, of the variability in currency returns compared to the contribution of approximately 8% from the prices of carry and momentum risk.